Metabolic and Biosynthetic Diversity in Marine Myxobacteria - Gemperlein, Katja (Mar Drugs, 2018)
Prior to 2005, the vast majority of characterized myxobacteria were obtained from terrestrial habitats. Since then, several species of halotolerant and even obligate marine myxobacteria have been described. Chemical analyses of extracts from these organisms have confirmed their ability to produce secondary metabolites with unique chemical scaffolds. Indeed, new genera of marine-derived myxobacteria, particularly Enhygromyxa, have been shown to produce novel chemical scaffolds that differ from those observed in soil myxobacteria. Further studies have shown that marine sponges and terrestrial myxobacteria are capable of producing similar or even identical secondary metabolites, suggesting that myxobacterial symbionts may have been the true producers. Recent in silico analysis of the genome sequences available from six marine myxobacteria disclosed a remarkably versatile biosynthetic potential. With access to ever-advancing tools for small molecule and genetic evaluation, these studies suggest a bright future for expeditions into this yet untapped resource for secondary metabolites.